1981
DOI: 10.1002/j.1552-4604.1981.tb02627.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in Glaucoma: A Primary Screening Procedure

Abstract: A procedure was developed for screening of cannabinoids for their ability to reduce intraocular pressure (lOP) using normal rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Most of these studies also reported various systemic side effects, such as hypotension, tachycardia, euphoria, and dysphoria, as well as other ocular effects, such as changes in pupil size, decreased tear production, and conjunctival hyperemia. Endocannabinoids and synthetic cannabinoid ligands have also been reported to reduce intraocular pressure when given topically or systemically, both in animals and humans (Shapiro, 1974;ElSohly et al, 1981ElSohly et al, , 1984Colasanti et al, 1984a,b,c;Pate et al, 1995;Porcella et al, 1998;Buchwald et al, 2002;Laine et al, 2002a,b;reviewed in Jarvinen et al, 2002;Chien et al, 2003;Tomida et al, 2004).…”
Section: E Eye Disorders (Glaucoma and Retinopathy)mentioning
confidence: 99%
“…Most of these studies also reported various systemic side effects, such as hypotension, tachycardia, euphoria, and dysphoria, as well as other ocular effects, such as changes in pupil size, decreased tear production, and conjunctival hyperemia. Endocannabinoids and synthetic cannabinoid ligands have also been reported to reduce intraocular pressure when given topically or systemically, both in animals and humans (Shapiro, 1974;ElSohly et al, 1981ElSohly et al, , 1984Colasanti et al, 1984a,b,c;Pate et al, 1995;Porcella et al, 1998;Buchwald et al, 2002;Laine et al, 2002a,b;reviewed in Jarvinen et al, 2002;Chien et al, 2003;Tomida et al, 2004).…”
Section: E Eye Disorders (Glaucoma and Retinopathy)mentioning
confidence: 99%
“…A8-THC, cannabinol, and nacilone were less hypotensive then A -THC and the effects were not dose-related (11). Naboctate given orally to rabbits lowered IOP; given orally to rats it caused mild tachycardia and mild systemic hypotension (151).…”
Section: Cannabinoidsmentioning
confidence: 98%
“…The synthetic compound nabilone (0.25 and 0.5 mg/kg) given intravenously in rabbits, significantly decreased IOP but behavioral changes in animals were evident (11).…”
Section: Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…THC, CBN, and nabilone were active in lowering intraocular pressure (IOP) in rabbits, while CBD was inactive. 235 Certain derivatives of THC were more active in lowering IOP than the parent cannabinoid 236 ; some topically used soft analogs that have no systemic effects were also active in IOP reduction. 237 The effect on IOP of 2-AG was biphasic (ie, an initial increase in IOP followed by a reduction).…”
Section: Asthma Cardiovascular Disorders Glaucomamentioning
confidence: 99%